The Dangers of Idealized Femininity in Early Modern Sophonisba Tragedies - DeLuca, Laura (Early Theatre, 2025)
This article examines early modern English dramatic representations of Carthaginian noblewoman Sophonisba as a model of idealized, white femininity. Through an analysis of John Marston’s The Wonder of Women, Thomas Nabbes’s Hannibal and Scipio, and Nathaniel Lee’s Sophonisba, or Hannibal’s Overthrow, I argue that Sophonisba’s chaste, fair body functions as the embodiment of idealized femininity while paradoxically exerting destabilizing power over men such as Masinissa, Syphax, and Scipio. These plays illuminate the irony of glorifying white, virginal femininity, which ultimately disrupts military and political pursuits.